The security environment in the Asia-Pacific: the context for arming - Bitzinger, Richard A. (2022)
Countries in the Asia-Pacific have many reasons for acquiring new defense hardware and improving national military capabilities. The region is clearly one of constantly shifting security dynamics, with rising great powers, new threats and security challenges, and new military commitments. All of these require new capabilities for power projection, mobility, firepower, intelligence and surveillance, and joint operations, thereby driving regional military modernisation. Consequently, some of the most modern and most advanced armaments are finding their way into the inventories of Asian militaries. Many regional militaries have experienced a significant, if not unprecedented, build-up in terms of both quantity and quality, over the past several years. Recent acquisitions by regional armed forces constitute something more than mere modernisation; rather, the new types of armaments being procured and deployed promise to significantly expand regional maritime and airborne warfighting capabilities.